CHANGE AND ADAPTATION IN THE COMMERCIAL SECTOR OF OSUN DIVISION, WESTERN NIGERIA, 1900-1960 (2014)
The advent of colonialism in Osun Division occasioned changes which impacted greatly on the commercial sector of the division. This is well attested by the remarkable adaptation of the sector to the changes. Issues relating to change and adaptation in the commercial sector have been neglected by the available studies on Osun Division. This study, therefore, examinedchange and adaptation in the commercial sector of Osun Division in the areas of transportation, currency, banking and entrepreneurship between 1900 and 1960 with a view to ascertaining how the colonial innovations were integrated into the Yoruba commercial practices. This study adopted the historical approach. Oral interviews were conducted with 30 purposively selected key informants. They comprised kings and chiefs,former railway officials and passengers, artisans and traders whose ages ranged from 68 to 120 years. Interviews were carried out in major towns of Osogbo, Ikirun, Inisa, Okuku, Ejigbo, Ogbomoso, Gbongan, Ede and Iwo. Archival materials were derived from the National Archives, Ibadan and Sopolu Library, Ikenne. These included Colonial Secretary's Office papers, Government gazettes together with annual and intelligence reports. Town Series and maps were collected from relevant government ministries in Osogbo and Ibadan. Data were subjected to historical analysis. People of Osun Division adapted in diverse ways to the changes introduced by colonialism. In the area of transportation, extension of railway to Osogbo in 1907 and the subsequent construction of feeder roads elicited massive emigration of people to other parts of Nigeria and further to West African countries like Republic of Benin, Togo, Ghana and Cote d'Ivoire. This stimulated international trade in which the people of Osun Division were well known. New markets and urban centres emerged around the railway stations in Iwo, Ile-ogbo, Kuta, Yawu, Origo, Ede, Osogbo, Ikirun, Inisa and Okuku. Around these stations, human porterage became commercialised with the emergence of the alabaru who were mostly women. The need to have the new money introduced in 1904gave birth to currency counterfeiting by the smart blacksmiths, who used their local technology to forge British coins. Traders were lured to more lucrative businesses of cash crops and imported items in order to gain more profits. Inadequacies in the operations of the BritishBank of West Africa established in Osogbo in 1924 made sogundogoji, a hybrid of the pre-colonial Iwofa credit and modern banking systems to emerge in order to provide greater amount of money for traders and other needy individuals. In the system dominated by European and Levantine firms, indigenous entrepreneurs assumed the roles of distributors of European merchandise andagents of cash crop trade. As indigenous aids to trade complemented the foreign ones, the volume of local and international trade increased. This led to the emergence of commercial elite who became a force to reckon with in the politics of Western region. The Cooperative Produce Marketing Union they formed influenced government policies for better cocoa prices and protection of members from exploitation. Change and adaptation in the commercial sector of Osun Division of Western Nigeria during the colonial period occurred in respect of transportation, currency, banking and entrepreneurship. The outcome was a hybrid that was partly traditional and partly modern. Nevertheless, indigenous commerce thrived simultaneously with foreign trade.